Self-diffusion and interactions in mixtures of imidazolium bis(mandelato)borate ionic liquids with polyethylene glycol (1) H NMR study - Filippov, Andrei (Magnetic resonance in chemistry : MRC, 2015)
Copyright © 2015 John Wiley & Sons, Ltd.